Enhanced Protease Production from Diabetic Ulcer-Derived E. coli: Peningkatan Produksi Protease dari E. coli yang Berasal dari Ulkus Diabetes - Mustafa Talib Muhsin (Universitas Muhammadiyah Sidoarjo, 2024)
This study explored a local Escherichia coli isolate from diabetic foot ulcer patients for protease enzyme production. Qualitative screening on skim milk agar showed a 6 mm hydrolysis halo, while quantitative screening with casein revealed a specific activity of 144.55 U/mg protein. Purification via ion exchange chromatography on DEAE-cellulose increased the specific activity to 767.5 U/mg, with a 5.3-fold enhancement and a 29.5% yield. The findings suggest E. coli as a viable source for protease production and demonstrate the efficiency of ion-exchange chromatography for enzyme purification, with potential significant industrial applications. Highlight: E. coli sourced from diabetic ulcers shows promise for protease production. Skim milk agar and casein used for qualitative and quantitative screening. Ion exchange chromatography significantly enhances enzyme specific activity. Keywoard: Escherichia coli, protease production, diabetic foot ulcer, enzyme purification, ion exchange chromatography